PERLINDUNGAN HUKUM BAGI ANAK YANG LAHIR DARI PERKAWINAN SEDARAH (INCEST) - Mega Suryaningati (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTSocially incest marriage is often found in the community, this is evidenced by the many reports in the media such as electronics, print media, and online articles. Based on the above reality, it is fitting to have a deeper discussion in analyzing the position of children resulting from incest marriages in the Indonesian Civil Law and Marriage Law to determine the extent of the status of the child and the inheritance problem of a child born because of incest marriages before the law in force in this country.This type of research used in this study is a type of normative legal research, which is a legal research method that uses a statutory approachThe results showed that the granting of protection to children in civil law regulates the rights of their citizens. Children are like adults as members of society, children also get rights. However, children cannot protect their rights like adults, therefore adult assistance is needed to take care of their rights. Therefore child protection is very important. Status or Position of Children of Incest according to the Indonesian Criminal Code, Marriage Law and Compilation of Islamic Law are as follows: According to Indonesian marriage law, namely Marriage Law, Islamic Law Compilation or KUHPdt, the status or position of children has divided into two namely legal children and illegitimate children Discordant children are children of fathers and mothers who cannot be married because of the close family ties between father and mother. Such children, by article 867 K UH Civil, have no right at all to inheritance from their parents and as much as possible only get enough income to live (het nodige / evensonderhoud). the article was reinforced by article 283 of the Civil Code which prohibits the recognition of such children Keywords: Legal protection, Marriage, Incest